Consumer Perceived Value and Halal Food Products Consumption in the Indonesia and Russia - Muhammad Asnan Fanani, Nur Asnawi,Abdul Haris, Nariman Shamakov (International Journal of Advanced Science and Technology, 2020)
Purpose - The importance of halal food products in the Islamic lifestyle bases the investigation on the pattern of Muslim’s behavior of product consumption in the majority and minority Muslims market as the primary goal. The hypothesis is an integration of the Perceived Value (PV) concept to determine the behavioral outcome (Theory of Planned Behavior-TPB) in consuming halal food products.